Biochanin A and its possible involvement in Parkinson’s disease management - Amninder Kaur; Simran Kaur; Amir Mushtaq; Diksha Dalal; Shubham Kumar; Anish Singh (Exploration of Neuroscience, 2025)
Parkinson’s disease is typified by Lewy bodies and the selective death of dopaminergic neurons in the substantia nigra. α-Synuclein aggregation, neuroinflammation, mitochondrial dysfunction, and oxidative stress are key components of its pathophysiology. The neuroprotective potential of natural substances with anti-inflammatory and antioxidant qualities has drawn attention in recent years. A naturally occurring isoflavone that is mostly present in red clover and other legumes, biochanin A has shown promise as a treatment option for Parkinson’s disease. Preclinical research has shown that biochanin A uses a variety of methods to provide notable neuroprotective benefits. By activating the Nrf2/ARE pathway, it scavenges reactive oxygen species (ROS), upregulates antioxidant defense enzymes, and inhibits pro-inflammatory mediators by modifying the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling cascade. Additionally, it has been demonstrated that biochanin A preserves neuronal integrity in Parkinson’s disease models by reducing dopaminergic neuronal death, inhibiting microglial activation, and mitigating mitochondrial dysfunction. Its potential as a neurotherapeutic agent is increased by its capacity to pass the blood-brain barrier. To investigate its safety, bioavailability, and effectiveness in people, more translational and clinical research is necessary. Biochanin A’s incorporation with neuroprotective techniques may pave the way for novel supplementary treatments for Parkinson’s disease. Therefore, the current review aims to present a thorough investigation of the molecular basis of biochanin A’s anti-Parkinson properties in Parkinson’s disease, building on the body of existing research that explains these properties.